2010
DOI: 10.1590/s0101-31222010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Physiological maturity of seeds and colorimetry of fruits of Jatropha curcas L.

Abstract: -The objective was to relate the coloration of fruits of Jatropha curcas L during the maturation process with morphometric (fruits and seeds) and germinative characteristics (seeds). Fruits were collected at various maturation stages from mast trees located in Eldorado/MS, and six maturation stages were visually classified based on fruit's epicarp color. Epicarp digital colorimetry was used to characterize maturation stages in addition to morphometric variables of length and width of fruits and seeds, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 10 publications
2
19
0
14
Order By: Relevance
“…Published studies with several species showed germination differences in relation to fruit maturation such as with Jatropha curcas L. (Dranski et al, 2010), Eugenia pyriformis Cambess and Eugenia involucrata DC. (Oro et al, 2012).…”
Section: Germination Testmentioning
confidence: 99%
“…Published studies with several species showed germination differences in relation to fruit maturation such as with Jatropha curcas L. (Dranski et al, 2010), Eugenia pyriformis Cambess and Eugenia involucrata DC. (Oro et al, 2012).…”
Section: Germination Testmentioning
confidence: 99%
“…A coloração dos frutos foi recomendada por Silva et al (2009) Dranski et al (2010), para sementes de pinhão-manso.…”
Section: Coloração Dos Frutos Parâmetros Avaliadosunclassified
“…Kole & Gupta (1982) e Maeda et al (1987) verificaram que o teor de óleo de sementes de girassol está fortemente relacionado com sua maturidade e que pode ser também um parâmetro importante para a escolha do momento da colheita, evitandose perdas relacionadas com o rendimento em óleo. Dranski et al (2010) observaram que frutos de pinhão-manso com epicarpo de coloração amarela com manchas marrons, apresentaram máximo acúmulo de matéria seca, teor de água inferior a 38,5% e sementes no ponto de maturidade fisiológica. No entanto, os autores não quantificaram o rendimento em óleo das sementes.…”
Section: Introductionunclassified
“…Thus, obtaining high-quality seeds has great importance, and this factor is affected by suitable harvest time, which for J. curcas is based on the outside colour of the fruits, with yellow and brownishyellow fruits being the most recommended (Dranski et al, 2010;Silva, Dias, Milagres, & Dias, 2012;Sowmya, Gowda, Balakrishna, & Rao, 2012). At these stages, the seeds are near the physiological maturity point .…”
Section: Introductionmentioning
confidence: 99%